PARTISIPASI MASYARAKAT DALAM PEMBENTUKAN PERUNDANGÂUNDANGAN UNTUK MEWUJUDKAN NEGARA KESEJAHTERAAN INDONESIA - S., Laurensius Arliman (Jurnal Politik Pemerintahan Dharma Praja, 2017)
ABSTRACT In the country of law, the law is one form of legal norms formulation in the life of the state. The existence of laws in a country has a strategic and important position, regardless of the conception of the law, hierarchy of legal norms, as well as from the function of law in general. People’s welfare is one of the goals of the state. In the realization of the necessary mechanisms are reflected in the public policy that is made. This study aims to examine and examine the public participation in the formation of legislation to create the welfare state of Indonesia. The research of this scientific work, the type of normative legal research. The understanding of the welfare state can be applied in the formulation of legislation. Welfare is the dream of every society, and laws and regulations function as regulators and means of achievement. To realize the formation of responsive legislation in Indonesia, the formation of legislation in Indonesia must be subject to Article 5 and Article 6 of Law Number 12 Year 2011 on the Establishment of Legislation, And this is related to the formation of Legislation and adheres to the principles of the establishment of good legislation. So the welfare state can be realized. Keywords: participation, society, law, welfare state, Indonesia.